Circadian Patterns of Ingestion and Rumination in Ruminants: A Chronophysiological Review - Nikkhah, Akbar (Journal of Buffalo Science, 2019)
Grazing occurs mainly around sunrise and sunset. The time spent eating during the dusk grazing bout appears to be longer than that during the dawn and afternoon bouts. The rumen fill has likely a more significant role in regulating the dusk feed intake compared to dawn and afternoon feed intakes. The evening instead of morning feed delivery in once daily fed lactating dairy cows has increased eating rate and the amount of feed ingested within 3-h post-feeding substantively. Evidently, feeding strategies and systems regulate feed intake through altering circadian rhythms of feed intake in high-producing ruminants. The large evening meals in grazing cows have partly been linked to an optimal foraging strategy. Ruminants attempt to optimize their nutrient intake profile by filling the rumen in the evening because usually little grazing occurs overnight. Turning lights on and off seems to act as an inducer, thus stimulating eating activity. Dairy cows fed once daily at 2100 vs. 0900 h have experienced a larger rumen volume. The greater rumen contents or greater rumen fiber load may stimulate bolus formation required for rumination. The greater rumen contents or greater rumen fiber load may stimulate bolus formation required for rumination. Future research is warranted to quantify how different managements can manipulate eating and ruminating patterns in dairy and beef ruminants undergoing varying physiological states.